Cryptococcosis: a consequence of Cryptococcus neoformans infection in AIDS patients in Brazil (Research, Society and Development, 2021)
This research aims to understand the consequences of infection by Cryptococcus neoformans in patients with AIDS in Brazil, as well as to understand the development of C. neoformans in people with AIDS and highlight the diagnosis, symptoms and treatment of cryptococcosis. The present study consists of integrative bibliographic research with the main sources: articles, theses scientific journals electronic magazines. The digital platform seeks form: Scientific Electronic Library Online (SCIELO), Latin American and Caribbean Literature on Health Sciences (LILACS), Virtual Health Library (VHL) and Google Scholar. The inclusion criteria published within the estimated period are studies published between 2012 and 2021 that appear in the Portuguese english languages. Exclusion criteria were articles that do not address the conniving ideas of the work, repeated articles or with insufficient data and that does not fit the objective of the research. It was concluded that the opportunistic infection of C. neoformans presented result in the obtained of HIV-infected patients. In these cases, treatment in HIV-infected patients with cryptococcosis initially occurs, deporting antiretroviral therapy within 5 weeks, after antifungal therapy is initiated. However, in the course it is necessary to be careful with the control of intracranial pressure for cryptococcal meningitis and the supply of ARVs to restore immune function are necessary for the treatment to be successful. Finally, it is noteworthy that it is necessary to invest in health so that the early diagnosis of the fungus C. neoformans is made quickly and helpfully for this public, since this fungus is characterized as opportunistic.